Answer:
Equation -3x² - x + 3 = -3x² can not be solved using quadratic formula.
Explanation:
1. -3x² - x + 3 = -3x²
Simplify above equation,
-3x² + 3x² - x + 3 = 0
or -x + 3 = 0 , Sine x² terms cancelled each other.
Hence this equation can not be solved using quadratic formula.
2. 0 =x² , yes here we can use quadratic formula
3. 0 = 2x²-1
Simplifying the above equation,
0 = 2x² - 1
1 = 2x²
x² =
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
Hence we can use quadratic formula here.
4. x²+3x-2 = 4x²- 5x - 1
Simplifying given equation,
x²+3x-2 = 4x²- 5x - 1
or x² - 4x² +3x +5x -2 + 1 = 0
or -3x² + 8x - 1 = 0
since x² term is here, hence we can solve this using quadratic formula.